Pembrolizumab‐related pancreatitis with elevation of pancreatic tumour markers. Issue 2 (5th February 2020) - Kakuwa, Tamaki; Hashimoto, Masao; Izumi, Atsuko; Naka, Go; Takeda, Yuichiro; Sugiyama, Haruhito
Abstract : Lung cancer immunotherapy is an effective treatment option; however, it can be hampered by adverse events, including pancreatitis, associated with excessive immune activation. Here, we report the case of a 70‐year‐old patient who presented with recurrent lung squamous carcinoma and was started with pembrolizumab treatment (200 mg every three weeks). The patient developed pembrolizumab‐induced pancreatitis. After 14 months of pembrolizumab treatment, positron emission tomography–computed tomography showed a tumour‐shaped, highly integrated lesion at the pancreatic head and significantly elevated tumour markers, including carbohydrate antigen 19‐9 (149.3 U/mL), s‐pancreas antigen‐1 (44.7 U/mL), and duke pancreatic monoclonal antigen type 2 (412 U/mL). Pembrolizumab‐induced immune‐related pancreatitis was effectively treated with prednisolone 90 mg (1 mg/kg/day). Four months later, normal levels of the three specific tumour markers were detected, with improved pancreatic enzymes and radiographic findings. To our knowledge, this is the first reported case of immune‐related pancreatitis with elevated pancreatic cancer‐specific markers. Abstract : We report a case of pembrolizumab‐induced immune‐related pancreatitis with the elevation of pancreatic tumour markers in a patient with squamous cell lung cancer.